Kajian Literature: Peranan Etika Dalam Suatu Perusahaan Bisnis - Devinda Ramdani; Ameliya Ameliya; Agum Murtaib; Agustiawan Agustiawan (Universitas 45 Surabaya, 2024)
The purpose of this research is to identify the role of business ethics in the corporate context. The method used in this research is a literature review, which is based on experts' views regarding business ethics and its contribution to the corporate environment. Business ethics can be applied in various aspects. Maintaining trust in collaboration has a significant impact on a company's reputation, both on a micro and macro scale. While it may not provide instant profits, it is considered a long-term investment for the entire business chain.